2000
DOI: 10.1007/s100380050210
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning, tissue expression, and chromosome mapping of human homolog of SOX18

Abstract: The SRY (sex-determining region Y) gene encodes a transcription factor characterized by a DNAbinding motif termed the HMG (high mobility group) domain. The SOX (Sry-box) genes comprise a large family related by homology to the HMG-box region. We isolated a cDNA clone with an open reading frame encoding a putative protein of 384 amino acids, which shared 83% identity to the mouse Sox18 protein. Northern blot analysis revealed that a 1.9-kb band of human SOX18 messenger RNAs was predominantly expressed in heart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Other studies have shown a critical role for Sox proteins in sex determination (Jennifer and Marshall, 1998), as well as in the proper development of the central and/or peripheral nervous system (Connor et al, 1995;Tani et al, 1997;Pevny and Lovell-Badge, 1997). Evidence of the expression of Sox18 in the brain (Azuma et al, 2000), as well as Sry in midbrain (Wegner, 1999), makes it plausible that Sox18 regulation could mediate known sex differences in mor expression. Therefore, it is tempting to propose that dual promoters could be a mechanism for sexually dimorphic gene regulation by Sox factors, to provide sex differences in pain responses and in the effectiveness of various analgesic agents that act on opioid receptors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have shown a critical role for Sox proteins in sex determination (Jennifer and Marshall, 1998), as well as in the proper development of the central and/or peripheral nervous system (Connor et al, 1995;Tani et al, 1997;Pevny and Lovell-Badge, 1997). Evidence of the expression of Sox18 in the brain (Azuma et al, 2000), as well as Sry in midbrain (Wegner, 1999), makes it plausible that Sox18 regulation could mediate known sex differences in mor expression. Therefore, it is tempting to propose that dual promoters could be a mechanism for sexually dimorphic gene regulation by Sox factors, to provide sex differences in pain responses and in the effectiveness of various analgesic agents that act on opioid receptors.…”
Section: Discussionmentioning
confidence: 95%
“…Sox proteins have critical roles in the regulation of numerous developmental pathways, such as those of epithelium-derived tissues, including the nervous system (Connor et al, 1995;Lefebvre et al, 1997;Tani et al, 1997;Wegner, 1999), T-cell differentiation (Van de Wetering et al, 1993;Wotton et al, 1995), and bone formation and gonadogenesis (Lefebvre et al, 1997;Pevny and Lovell-Badge, 1997;Wegner, 1999). Recently, the expression of Sox18 in the CNS has been reported (Azuma et al, 2000), although its role in regulating particular CNS genes has hitherto been unknown. Therefore, the mor gene is, to the best of our knowledge, the first reported Sox18 target gene expressed in brain.…”
mentioning
confidence: 99%
“…Cloning of these SOX proteins from the adult mouse brain cDNA library indicates that the expression of these SOX genes is not only restricted to early central nervous system development (31)(32)(33)(34), but these genes are also expressed in the adult mouse brain. Although none of these proteins is strictly expressed in the central nervous system (31-34), the co-existence of SOXes and MOR in the central nervous system provides the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have reported a critical role for SOX proteins in sex determination (49) as well as in the proper development of the central and/or peripheral nervous system (12,32,50). In addition, Sox18 is expressed in fetal brain (34) and also expressed weakly in adult brain (33). The Sox21 gene is highly conserved and specifically expressed in the brain (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…7 These include 10 genes encoding crystallins (CRYAA, CRYAB, CRYBA1/ A3, CRYBA, CRYBB1, CRYBB2, CRYBB3, CRYGC, CRYGD, CRYGs), three encoding membrane transport proteins (MIP, GJA3, GJA8), two encoding a cytoskeletal protein (BSFP2, BFSP1), three encoding transcription factors (HSF4, MAF, PITX3), one encoding a lens intrinsic membrane protein (Lim2), one encoding a chromatin modifying protein (CHMP4B), one encoding a protein-tyrosine kinase protein (EPHA2) and other genes forkhead box E3(FOXE3), eyes absent homolog 1(EYA1). [7][8][9][10][11][12][13] The crystallin genes encode more than 90% of the water-soluble structural proteins present in the vertebrate crystallin lens and clearly represent compelling candidate genes for congenital cataracts.…”
mentioning
confidence: 99%